MAP3K8 kinase regulates myeloma growth by cell‐autonomous and non‐autonomous mechanisms involving myeloma‐associated monocytes/macrophages. (18th December 2012) - Hebron, Ellen; Hope, Chelsea; Kim, Jaehyup; Jensen, Jeffrey L.; Flanagan, Claire; Bhatia, Neehar; Maroulakou, Ioanna; Mitsiades, Constantine; Miyamoto, Shigeki; Callander, Natalie; Hematti, Peiman; Asimakopoulos, Fotis
Summary Benefit from cytotoxic therapy in myeloma may be limited by the persistence of residual tumour cells within protective niches. We have previously shown that monocytes/macrophages acquire a proinflammatory transcriptional profile in the myeloma microenvironment. Here we report constitutive activation of MAP3K8 kinase‐dependent pathways that regulate the magnitude and extent of inflammatory activity of monocytes/macrophages within myeloma niches. In myeloma tumour cells, MAP3K8 acts as mitogen‐induced MAP3K in mitosis and is required for TNFα‐mediated ERK activation. Pharmacological MAP3K8 inhibition results in dose‐dependent, tumour cell‐autonomous apoptosis despite contact with primary stroma. MAP3K8 blockade may disrupt crucial macrophage‐tumour cell interactions within myeloma niches.